Effects of configuration and headspace wind profile on the performances of flux chambers in gas emission measurement: a laboratory study - Ding, J.; Wang C; Lu Q; Yan Z; Shi Z (American Society of Agricultural and Biological Engineers, 2013)
Naturally ventilated building with an outdoor exercising area is a typical system for housing the dairy cattle in China, and it is still a challenge to find a technical solution to accurately measure gas emissions from the open yard directly. Chamber technique has been approved to be a potential way, while the configuration and change of the environmental condition in headspace of the chamber, wind profile in particular, may result in a systematic error and is not clearly specified yet. Three unvented cylindrical non-steady state flow-through chambers with different configurations were made and tested by using SF6 as a tracer gas, and impact of the chamber size and wind profile in the headspace was evaluated in this study. Results showed that the chamber measured and referred SF6 fluxes had a significant linear relationship. Footprint area of the chamber didn’t affect the measurement, while the height had a significant influence on its performance. It might because that the higher chamber reduced the effect of additional air-fill volume in emitting source below the chamber and hence increased the measuring accuracy. Wind speed and positive pressure generated by the mixing fan in the headspace had no significant impact on the measurement performance of the chamber. It may be explained by the offset effect between wind speed and positive pressure generated by the mixing fan inside the chamber, which could be verified in further studies.